Integration of family planning into the primary health care in Ethiopia: results from national assessment - Meselech Assegid Roro; Yohannes Mehretie Adinew; Senait Seid Yimer; Naod Firdu Gizaw; Abiy Seifu Estifanos; Jemal Kassaw Mohammed; Addisalem Titiyos Kebede; Kathryn A. O’Connell; Bilal Shikur Endris (Reproductive Health)
Abstract Background Family planning (FP) is part of Ethiopia’s essential health service package. However, integrating FP into other health care services is a relatively new concept. Integrated service can minimize missed opportunities and allow health workers to provide FP services and Reproductive, Maternal, Newborn, Child, Adolescent, and Nutrition (RMNCAH-N) services simultaneously. Thus, the objective of this study was to assess the levels of FP integration into maternal and child health (MCH) services at primary health care service delivery units in Ethiopia. Methods This was a facility-based cross-sectional study conducted from July to October 2022. We conducted a nationally representative survey of primary health care (PHC) facilities selected from seven regions and two-city administrations in Ethiopia to assess the current level of FP integration across four service delivery units (antenatal care unit, postnatal care unit, post-abortion care unit, and immunization unit) of the facilities. We collected data from selected health facilities through interview with health facility managers, healthcare providers in the selected service units, clients seeking health services, and extraction of data from facility records. We employed descriptive analysis, and categorized the degree of FP integration according to the FP information and services provided in the selected service delivery units. Results This national FP integration survey included 122 health facilities (39 primary hospitals, 42 health centers, and 41 health posts) from seven regions and two city administrations. The study found a huge discrepancy regarding FP counselling given at ANC, PNC, PAC, and immunization service delivery units as reported by health care providers and clients. The proportion of PNC and immunization clients who received FP counselling was higher at health post compared to hospitals and health centers. Moreover, the proportion of PAC clients who received FP information was higher in primary hospitals compared to health centers. Conclusion Data from facility records and provider interviews showed significant FP integration within ANC, PNC, and immunization units of PHC facilities. However, client exit interviews indicated low FP counselling integration. Facility records revealed few PNC and PAC clients received contraceptives in the past year. The study found high FP counselling and provision of at least one short- or long-acting contraceptive at PNC and PAC units. No facility offered contraceptives at immunization units, indicating missed FP integration opportunities.